2020
DOI: 10.1108/ssmt-10-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hourglass shape solder joints on underfill encapsulation process: numerical and experimental studies

Abstract: Purpose In line with the recent development of flip-chip reliability and underfill process, this paper aims to comprehensively investigate the effect of different hourglass shape solder joint on underfill encapsulation process by mean of experimental and numerical method. Design/methodology/approach Lattice Boltzmann method (LBM) numerical was used for the three-dimensional simulation of underfill process. The effects of ball grid arrays (BGA) encapsulation process in terms of filling time of the fluid were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Both the main constituents in underfill fluid of epoxy resin and silica fillers were separately considered to establish a two-way fluid-solid interaction with the aim to visualize the epoxy flow and filler particle distribution during the underfill flow stage [5]. On the contrary, other numerical studies on filler distributions were either based on the cured underfill package [64] or at the completion of underfilling [65] In the recent years, particle-based LBM was used to simulate the underfill flow, which had seen various applications in conventional capillary underfill [12,17,45,46,48,66,67], mold underfill [68,69], and pressurized underfill [70]. While both LBM and FVM numerical findings are comparable in terms of flow visualization and filling time aspects, it is reported that LBM-based simulation can simulate the void formation during underfill flow for which FVM-based simulation is incapable to achieve [46].…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Both the main constituents in underfill fluid of epoxy resin and silica fillers were separately considered to establish a two-way fluid-solid interaction with the aim to visualize the epoxy flow and filler particle distribution during the underfill flow stage [5]. On the contrary, other numerical studies on filler distributions were either based on the cured underfill package [64] or at the completion of underfilling [65] In the recent years, particle-based LBM was used to simulate the underfill flow, which had seen various applications in conventional capillary underfill [12,17,45,46,48,66,67], mold underfill [68,69], and pressurized underfill [70]. While both LBM and FVM numerical findings are comparable in terms of flow visualization and filling time aspects, it is reported that LBM-based simulation can simulate the void formation during underfill flow for which FVM-based simulation is incapable to achieve [46].…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Among these approaches, the solder bump interface stands out as a promising bonding technology due to its capacity for achieving a high-density connection, coupled with proficient electrical conductivity and effective heat dissipation in flip-chip technology [4]. Nonetheless, the advancement of flip-chip technology is confronted by a significant reliability hurdle, the occurrence of voids or sluggish filling within the solder bumps positioned between the silicon chip and the organic substrate [5][6][7][8]. This predicament can give rise to gradual underfilling processes, imposing substantial stresses on the solder bump interconnects.…”
Section: Introductionmentioning
confidence: 99%
“…In the postunderfill stage, the interfacial adhesion of copper/underfill was studied (Andre et al, 2020). Subsequently, the underfill flow in the package was modelled numerically (Ishak et al, 2020;Nashrudin et al, 2020), experimentally (Huang et al, 2020) or analytically (Ng et al, 2020). The void defect formed during the underfilling flow was also numerically simulated (Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%